Improvement of minority carrier lifetime in GaAs/AlxGa 1-xAs core-shell nanowires - Jiang, N; Parkinson, P; Gao, Q; Wong-Leung, J; Breuer, S; Tan, H; Jagadish, C (2012)
GaAs/AlxGa1-xAs core-shell nanowires were grown by metal organic chemical vapour deposition with Au-catalysed GaAs cores. Cross-section transmission electron microscope bright field images show that the tapering at bottom of the nanowires is mainly caused by GaAs cap growth. Time-resolved photo-luminescence measurements of single nanowires were taken at room temperature and a minority carrier lifetime of (1.02±0.43) ns was obtained for single nanowires with AlxGa1-xAs shell grown at 750°C. A close correlation between the shell growth temperature and minority carrier lifetime has also been observed. © 2012 IEEE.